Alterations in CNS-derived blood biomarkers during 30 days simulated microgravity - Susanne V. Schmidt; Alexandru Odainic; Alexandru Odainic; Benjamin Aretz; Petra Frings-Meuthen; Jan-Niklas Hoenemann; Jan-Niklas Hoenemann; Maria Bohmeier; Christian Liemersdorf; Edwin Mulder; Stefan Moestl; Karsten Heusser; et al. (Frontiers in Physiology)
IntroductionSpaceflight induces physiological adaptations, including headward fluid shifts that may impact the central nervous system (CNS). Ground-based analogs such as 6° head-down tilt bed rest (HDTBR) provide a controlled setting to study these neurophysiological effects and assess CNS biomarkers. We therefore analyzed neurological function and CNS-derived blood biomarkers during four NASA-backed 30-day strict HDTBR campaigns to better understand neurophysiological responses to prolonged fluid redistribution.MethodsForty participants (18 women, 22 men; mean age ∼36 years) were assigned to different countermeasure groups: lower body negative pressure (LBNP), cycling in HDT followed by wearing thigh cuffs, upright sitting (positive control), and HDTBR without countermeasures. Neurological exams and blood biomarker analyses (SIMOA Quanterix) were performed to assess NfL, GFAP, Aβ40, Aβ42, and total tau.ResultsNo clinical neurological impairments were observed. The LBNP group exhibited robust increases in amyloid-related biomarkers during HDTBR, which persisted into the recovery period. Analysis of within-subject changes over time revealed additional effects. In the cycling and cuffs group, NFL levels increased progressively throughout the study. In the control group, GFAP levels rose gradually, indicating mild glial activation. Tau protein also increased in the LBNP group but returned to baseline levels during the recovery phase.DiscussionThese findings highlight subtle but biologically relevant CNS-related changes in response to different countermeasure strategies during 30-day strict HDTBR. LBNP may enhance metabolite clearance, as reflected in increased Aβ washout. These findings support the use of LBNP as a potential countermeasure to protect brain health during spaceflight and analog missions.